Effect of Priming and Seed Size on Germination and Emergence of Six Food-Type Soybean Varieties - Maru K. Kering; Bo Zhang (International Journal of Agronomy)
Soybean (Glycine max (L.) Merr.), a good source of protein and oil, is used to produce nutritious isoflavone-rich soybean-based foods. The objectives of this study were (i) to determine the germination difference among soybean seeds in various seed sizes and (ii) to evaluate effects of seed pretreatment on germination and seedling emergence. Six varieties of different seed size class were used: (i) small size (MFS-561 and V08-4773), (ii) medium size (Glen and V03-47050), and (iii) large size (MFL-159 and V07-1897). Pregermination treatments include 0, 5, or 10 hours soaking and germinating/planting with or without nitrogen fertilizer. Large seed size varieties showed low germination rate and N addition caused the least reduction in germination in these seeds during the first 24 hours. While N had no effect on seed germination after 72 hours, growth in N treated seed was low. Seedling emergence was comparable across varieties in 2013 and water priming and N application had no effect. However, while varieties did not differ in final emergence for nonprimed seeds in 2014, water priming led to a high reduction in seedling emergence of large seed varieties in this study. Application of N fertilizer had no effect on seedling emergence in field experiments.